Pancreaticoduodenectomy with malrotation following reoperation due to torsion of efferent loop: a case report - Yumiko Kageyama; Ryuzo Yamaguchi; Shinya Watanabe; Keiji Aizu; Shinichiro Kobayashi; Fumiya Sato; Hironori Fujieda; Yoshitaka Toyoda; Tsutomu Iwata (Surgical Case Reports, 2020)
Abstract Background Malrotation is a congenital anomaly during the development of the embryonic intestine. Although it is generally considered a pediatric surgical condition, it can have significant implications for adult surgery in terms of reconstruction. Case presentation The patient was an 85-year-old man with pancreatic cancer and intestinal malrotation. He underwent pancreaticoduodenectomy with modified Child’s reconstruction. Because the ascending colon and efferent loop twisted easily, we fixed the ascending colon to the abdominal wall. Thereafter, right twist and stenosis of the efferent loop occurred. On the 22nd day after the initial surgery, detorsion and Braun anastomosis were performed for efferent loop fixation. Postoperative oral intake was good, and the patient was discharged from our hospital on the 24th day after the reoperation. Conclusions This is a rare case of pancreaticoduodenectomy with malrotation following reoperation due to a complication after Child’s reconstruction. In similar cases of intestinal malrotation, it is important to consider avoiding coaxial positioning of intestinal parts and an upper abdominal space while selecting a reconstruction method.